ChemInform Abstract: Palladium‐Catalyzed Domino Carbopalladation/C—H Activation for the Synthesis of Tetrasubstituted Alkenes Bearing Five‐ and Seven‐Membered Rings. Issue 4 (31st January 2013) - Tietze, Lutz F.; Hungerland, Tim; Depken, Christian; Maass, Christian; Stalke, Dietmar
Abstract Propargylic alcohols (I) afford tetrasubstituted alkenes having a dihydroindene‐ or a benzo[7]annulene motif.